Antibody modified porous silicon microparticles for the selective capture of cells - Guan, B.; Magenau, A.; Ciampi, Simone; Gaus, K.; Reece, P.; Gooding, J. (2014)
Herein, the ability of porous silicon (PSi) particles for selectively binding to specific cells is investigated. PSi microparticles with a high reflectance band in the reflectivity profile are fabricated, and subsequently passivated and modified with antibodies via the Cu(I)-catalyzed alkyne-azide cycloaddition reaction and succimidyl activation. To demonstrate the ability of the antibody-modified PSi particles to selectively bind to one cell type over others, HeLa cells were transfected with surface epitopes fused to fluorescent proteins. The antibody-functionalized PSi particles showed good selectivity for the corresponding surface protein on HeLa cells, with no significant cross-reactivity. The results are important for the application of PSi particles in cell sensing and drug delivery.